Photochromism of diarylethene-functionalized 7-deazaguanosines - Singer, Marco; Nierth, Alexander; Jäschke, Andres (European journal of organic chemistry, 2013)
In a prior report we introduced a novel class of photochromic nucleosides (PCNs) that combine the structural features of adenine with the photochromic properties of diarylethenes. Herein, we translated this concept to the nucleoside guanosine, generating reversibly switching guanosine-like PCNs. These switches consist of a 7-deazaguanosine unit and a second aryl functionality, which are linked through a cyclopentene unit. Irradiation of the open-form isomer with light at 300 nm induces a pericyclic reaction that can be reversed with visible light. In addition to optical stimulation, these switches respond to light-independent stimuli, such as the presence of acid or complexation with metal ions.
First published: 15 April 2013
Gesehen am 02.02.2022